The Sir Mortimer B. Davis Jewish General Hospital - Guttman, Frank Myron; Wright, Alexander (Archivist) (McGill-Queen's University Press, 2018)
A compelling look at the remarkable progress of Montreal's Jewish General Hospital, from a community hospital to a first-class medical and research centre.